KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DALAM MENYELESAIKAN SOAL HOTS - Akbar Taufik; Irfan Arsid (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
A matter of HOTS is one that can be used to measure students 'ability in problem solving, therefore in detail the purpose of this study is to find out how the students' mathematical problem solving ability in solving HOTS questions at SMK Nasional Makassar. The method used in this research is descriptive research. In data collection, two methods are used, namely the documentation method, in which this method will produce data in the form of student work, and the second is the interview method, in this interview, the researcher will explore how the students' responses and problem-solving abilities are. The stages to be carried out in this research include three steps: (1) the preparation stage; (2) the research implementation stage; (3) the preparation of a report. The result in this study is that the SMK Nasional Makassar students are still lacking in working on HOTS questions, this shows that less than 50% of students are able to answer up to 5 questions which are HOTS category questions. Where there were only 18 students who were able to answer 2 question numbers in the analyzing category and only 5 people who were able to answer in the evaluating category. While at the level of creating none of the students were able to answer correctly. This is because the ability and accuracy of students in analyzing and visualizing questions in the form of pictures is still lacking.